Vicarious ratings of self vs. other-directed social touch in women with and recovered from Anorexia Nervosa - Ashleigh Bellard; Paula Trotter; Francis McGlone; Valentina Cazzato (Scientific Reports, 2022)
Abstract Anorexia Nervosa (AN) is an eating pathology characterized by restricted eating, body image distortions and impaired socio-cognitive abilities. Altered responses to affective touch—a pleasant interoceptive stimulus hypothesised to involve activation of the C-Tactile (CT) system, may contribute to the aetiology and maintenance of this disorder. Here, we investigated whether third-party social touch vicarious ratings of different body sites at CT-optimal vs. non-CT optimal velocities differed in women with and recovered from AN (RAN) and healthy controls (HCs). Thirty-five HCs, 27 AN and 29 RAN provided pleasantness ratings for two different tasks designed to probe expectations of how touch is perceived by self (self-directed touch) vs. others (other-directed touch). Findings revealed that both clinical groups, compared to HCs, did not differ in their pleasantness ratings to touch for another but when evaluating touch for self, both clinical groups rated CT-optimal touch as less pleasant than HCs. These findings suggest that AN and RAN women demonstrate an atypical vicarious pleasantness response to affective touch involving self, but not others. Novel therapeutic approaches that help anorexics to better interpret or improve tolerance of affective tactile experiences involving the self may be an important addition to current standard treatments.